A 2′, 2′-disulfide-bridged dinucleotide conformationally locks RNA hairpins. Issue 17 (12th April 2018) - Gauthier, Florian; Beltran, Frédéric; Biscans, Annabelle; Debart, Françoise; Dupouy, Christelle; Vasseur, Jean-Jacques
Abstract : We report the effect of a 2′, 2′-disulfide bridge in the loop of the RNA hairpins and its application as a molecular beacon. Abstract : The synthesis and the impact of a disulfide bridge between 2′- O -positions of two adjacent nucleotides in an RNA duplex and in the loop of RNA hairpins are reported. The incorporation of this 2′, 2′-disulfide (S–S) bridge enabled thermal and enzymatic stabilization of the hairpin depending on its position in the loop. The influence of the disulfide bridge on RNA folding was studied at the HIV Dimerization Initiation Site (DIS) as an RNA sequence model. We have shown that this S–S bridge locked the hairpin form, whereas the extended duplex form was generated after the reduction of the disulfide bond in the presence of tris(2-carboxyethyl)phosphine or glutathione. Thus, the S–S bridge can be useful for understanding RNA folding; an RNA molecular beacon locked by an S–S bridge was also investigated as a sensor for the detection of glutathione.